Roles of housing wealth and financial wealth in monetary transmission mechanism in Malaysia - Cheah, Siew Pong; Law, Siong Hook (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study analyses the wealth channel of the monetary policy transmission mechanism in Malaysia. Given the underdevelopment and non-inclusion of housing wealth in previous literature regarding the wealth channel in Malaysia, this research aims to find out (1) whether monetary policy shocks significantly affect asset prices, (2) whether asset prices fluctuations have significant influences on household consumption, and (3) whether house prices and stock prices have significant and equivalent roles in the operation of the wealth channel. In order to fulfill the research objectives, this study employs a methodological framework of structural vector autoregression (SVAR). By constructing a SVAR model with 5 endogenous variables and 68 quarterly observations in Malaysia from 1999Q1 to 2015Q4, the findings support the positive impacts from monetary expansion to the asset price level, and later from asset price fluctuation on aggregate consumption spending in Malaysia. The effect of monetary policy is mainly transmitted through financial wealth, in particular, the stock market, whereas the contribution of housing wealth is virtually nil in the wealth channel.